2022
DOI: 10.1103/physrevlett.129.183601
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Properties of Entangled Two-Photon Absorption

Abstract: We experimentally study entangled two-photon absorption in rhodamine 6G as a function of the spatial properties of a high flux of broadband entangled photon pairs. We first demonstrate a key signature dependence of the entangled two-photon absorption rate on the type of entangled pair flux attenuation: linear, when the laser pump power is attenuated, and quadratic, when the pair flux itself experiences linear loss. We then perform a fluorescence-based Z-scan measurement to study the influence of beam waist siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…30,31 Furthermore, the electronic transitions of molecules and atoms are accessible at visible and near-IR wavelengths, allowing for fluorescence lifetime measurements, 8,32,33 compatibility with quantum memories, 34 and fundamental studies of few-photon nonlinearities. 20,35,36 Despite these advantages, all demonstrations of nanophotonic pair production have resided in the telecom region, and the best near-IR and visible photon pair sources are still large-area waveguides [37][38][39][40] and bulk periodically poled crystals. 20,35,37,[41][42][43][44] Potential reasons for this discrepancy stem from the difficulty in fabricating visible nonlinear circuits on thin-film lithium niobate due to factors such as the ultra-short poling periods required for quasi-phase matching and losses from material absorption [45][46][47] and scattering.…”
Section: High-flux On-chip Entangled Photon Sourcesmentioning
confidence: 99%
“…30,31 Furthermore, the electronic transitions of molecules and atoms are accessible at visible and near-IR wavelengths, allowing for fluorescence lifetime measurements, 8,32,33 compatibility with quantum memories, 34 and fundamental studies of few-photon nonlinearities. 20,35,36 Despite these advantages, all demonstrations of nanophotonic pair production have resided in the telecom region, and the best near-IR and visible photon pair sources are still large-area waveguides [37][38][39][40] and bulk periodically poled crystals. 20,35,37,[41][42][43][44] Potential reasons for this discrepancy stem from the difficulty in fabricating visible nonlinear circuits on thin-film lithium niobate due to factors such as the ultra-short poling periods required for quasi-phase matching and losses from material absorption [45][46][47] and scattering.…”
Section: High-flux On-chip Entangled Photon Sourcesmentioning
confidence: 99%
“…For entangled photon pair production, the best visible and NIR photon pair sources are still large-area waveguides [23][24][25][26] and bulk periodically poled crystals. 23,[27][28][29][30][31][32] Similarly for UV generation, the few reported devices have been limited to large-area waveguides, 33,34 nanoparticles, 35 and metasurfaces. 36 These previous works do not take advantage of the sub-µm mode confinement and efficiency of lithium niobate in a nanophotonic platform.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 The electronic transitions of molecules and atoms also become accessible at NIR wavelengths, allowing for fluorescence lifetime measurements, [50][51][52] compatibility with quantum memories, 53 and fundamental studies of few-photon nonlinearities. 30,32,54 More generally, UV, visible, and NIR photons can be detected with high quantum efficiency and low dark noise using existing mature silicon technology at room temperature, compared to NIR-IR detectors which require cryogenic cooling. 55 Here, we have fabricated TFLN periodically poled waveguides for entangled photon pair generation 56 and second harmonic generation.…”
Section: Introductionmentioning
confidence: 99%
“…, where T e is the coherence time, A is what is referred to as the entanglement area, which, in practical terms, corresponds to the area of the excitation beam, 18 and f is a correction factor that takes into account possible contributions such as the ratio between the pump and entangled photon bandwidths.…”
mentioning
confidence: 99%
“…In other studies, attempts have been made to put some bounds on expected values to gauge why some experiments observe ETPA and others do not. , This was also motivated by an attempt to understand the large variation–sometimes several orders of magnitude - in the observed values for some ETPA cross-sections, which built on the seminal work of Fei et al This focused on the connection between the observed and microscopic cross-sections ς e = f false⟨ σ e false⟩ A T e , where T e is the coherence time, A is what is referred to as the entanglement area, which, in practical terms, corresponds to the area of the excitation beam, and f is a correction factor that takes into account possible contributions such as the ratio between the pump and entangled photon bandwidths.…”
mentioning
confidence: 99%